STRUKTUR ANATOMI ORGAN VEGETATIF Pedada Merah (Sonneratia caseolaris (L.) Engler) DI HUTAN MANGROVE KENAGARIAN MANGGUANG KOTA PARIAMAN - Niken, Niken; Eka Putri, Irma Leilani; Meriko, Lince (Pendidikan Biologi, 2013)
ABSTRACT Sonneratia caseolaris is one mangrove plant species belonging to family Sonneratiaceae. Sonneratia caseolaris has three morphological variations are dwarf, semi-dwarf and normal. In connection with such variation has been studied to determine the anatomical structure of the vegetative organs pedada red (Sonneratia caseolaris (L.) Engler) in Mangrove Forests Kenagarian Mangguang Pariaman city. This study was conducted in January-February 2013 by using the descriptive method of making permanent preparations. Based on the results, the differences in the complexity of the tissues of the three variations Sonneratia caseolaris. At the root Sonneratia caseolaris dwarf and normal tissue there is a sklereid amplifier, whereas the semi-dwarf Sonneratia caseolaris reinforcements in the form of fiber tissues. In the third variation stems from Sonneratia caseolaris there is no difference but the similarity of the complexity of their tissues  covering cuticula thin epidermis, cortex, vascular tissue and pith while the third variation on the leaves of Sonneratia caseolaris difference is the semi-dwarf and normal Sonneratia caseolaris there is substance ergastict in the form of crystalline type drush , while the dwarf Sonneratia caseolaris not found. Another difference is in the normal Sonneratia caseolaris  the epidermis consists of 2 layers, on Sonneratia caseolaris dwarf and semi-dwarf only 1 layer and the normal Sonneratia caseolaris  palisade tissue consists of  2 layers while Sonneratia caseolaris dwarf and semi-dwarf 3 layers.